Load Disturbance Rejection Based PID Controller for Frequency Regulation of a Microgrid - Badal Kumar; Sandeep Bhongade (Institute of Advanced Engineering and Science, 2017)
Today’s world is very much concerned to reduce green house gas emission from the conventional thermal power plants as cutting down emissions from transport and heating sector may not be realistic in the near future. To reduce pollution from electrical power sources, the world is now marching towards usage of renewable energy sources (RESs). These sources being small in capacity are mostly connected at the distribution voltage level. This indirectly reduces transmission and distribution losses as the sources are around the load. This distribution system having small scale energy sources is called as a microgrid or active distribution network. Microgrid operates generally in a grid connected mode. However, circumstances such as fault, voltage sag and large frequency oscillations in the main grid may force the active distribution network to be disconnected from the main grid and operate as an isolated microgrid . During this isolation there will be change in power output from the controllable microsources which are to be regulated properly to have a stable operation in regard to power balance and frequency of operation within the isolated microgrid. An autonomous isolated microgrid comprising both controllable & uncontrollable sources. Like solar, wind, diesel generator(DG), aqua electrolyzer(AE), fuel cell(FC), a battery energy storage system(BESS), and fly wheel(FW) are considered. Solar, wind, DG and FC are power generating source & BESS, FW, AE as energy storage element. The generated hydrogen by an AE is used as fuel for a FC. The power system frequency deviates for the sudden change in load demand and the real power generation. The output power of DG, FC, BESS, FW and power absorbed by AE is regulated by using controller such that frequency of the system is controlled. Controller used is proportional plus integral plus derivative (PID). Load Disturbance Rejection(LDR) is used for tuning of controller gains of the proposed hybrid system. This uses the chien-hornes-resnick(CHR) setting with 20% overshoot. Design of p-f droop(frequency regulation parameter) for different controllable source in microgrid using bode plot stability criterion. The system response with Modified LDR based controller, LDR based controller and classical controller are compared. Investigation shows that Modified LDR based controller gives best response amongst these three methods.